The clinical value of systemic immune-inflammation index (SII) and prognostic nutritional index (PNI) for predicting the occurrence of metastasis in patients with lung cancer - Verna Biutifasari; Ellen Angelique Hardjono; Ronald Pratama Adiwinoto; Janto Poernomo Hadi (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2025)
Systemic immune-inflammation index (SII) and prognostic nutritional index (PNI) serve as simple and practical tests that help indicate inflammatory and nutritional status to some extent. Lung cancer stands out as the most common contributor to cancer-related mortality globally. It is associated with an unfavorable prognosis. Most patients diagnosed with lung cancer have metastasis at the time of diagnosis. Prognostic heterogeneity of cancer patients causes the need for more prognostic biomarkers. This study aimed to evaluate the clinical value of SII and PNI in predicting metastasis in lung cancer patients. SII and PNI provides a prognostic value in lung cancer. Retrospective cross-sectional research was conducted in this study involving 138 data from medical records at the Inpatient and Outpatient Department of Pulmonology, RSPAL dr. Ramelan Surabaya in April 2019 to July 2023. Kolmogorov-Smirnov test, contingency coefficient test, and ROC analysis were done to analyze the data obtained. Patients with metastatic lung cancer had higher SII than those without metastasis. The group of patients with metastasis had an average SII of 5391.34 and a PNI of 40.11. The group of patients without metastasis had an average SII of 2849.52 and PNI of 43.05. Lung cancer metastasis was correlated significantly with SII but not with PNI. The cut-off value was determined using the ROC curve. The cut-off value for SII was 2198.54 (68.5% sensitivity and 58.7% specificity) and for PNI was 42.2 (62% sensitivity and 54.3% specificity). SII was correlated with lung cancer metastasis and may be a promising indicator predicting of metastasis. PNI showed no significant correlation with lung cancer metastasis.